Utilization of Crystalline and Amorphous Silica as a Sintering Inhibitor in Iron/Iron Oxide Thermochemical Water Splitting Cycle - Al-Ragom, Fotouh (Frontiers in Chemical Engineering, 2021)
Hydrogen as a chemical fuel and energy carrier can provide the path to solar energy storage to overcome the intermittency issues. Hydrogen can be produced by various methods; among them is the thermochemical water splitting of metal/metal oxide reduction oxidization (redox) reactions. Many redox cycles were identified, including the non-volatile redox pair, such as the iron/iron oxide. This redox pair has the capability to produce hydrogen with rapid reaction rates especially when it is used in powder form due to the high specific reactive surface area. Yet, this pair suffers from sintering at temperatures exceeding 500 °C. Sintering adversely affects the hydrogen production process and inhibits the recycling of the powder. To overcome sintering, experimental investigations using elemental iron and silica were conducted as detailed in this paper. The oxidation of elemental iron (Fe) powder by steam to produce hydrogen was carried out using a fluidized bed reactor. The investigations aimed at developing a practical sintering inhibition technique that can allow repeated redox cycles, stabilize the powder reactivity, and maintain hydrogen production. The experimental investigations involved varying the fluidized bed temperature between 630-968 °C. The steam mass flow rate was set to 2 g/min. To inhibit sintering, solid-state mixing of crystalline, or amorphous silica with iron powder was used at various iron/silica volume fractions. The investigations showed that mixing iron with silica hinders the sintering but reduces the hydrogen yield. Mixing iron with crystalline silica with 0.5, 0.67 and 0.75 apparent volume fraction reduces the hydrogen yield compared to pure iron by 20%, 30% and 45%, respectively. Mixing iron with amorphous silica reduces the hydrogen yield by 35% and 45%, as compared to pure iron, for iron 0-250 µm and 125-355 µm particle size distribution respectively. The hydrogen production rate for iron/amorphous silica mixtures surpassed that of the iron/crystalline silica. Mixing iron with amorphous silica prevented sintering at elevated bed temperatures in the range of 850 °C and only clumping occurred. The clumped samples restored their original powder condition with minimum agitation. Thus, solid-state mixing of silica with iron powder can be a promising technique to retard iron particles sintering.